Philosophy and Sociology of Material Culture: Historical Reflection in the XXI Century Философия и социология материальной культуры: историческая рефлексия в XXI веке Філософія і соціологія матеріальної культури: історична рефлексія в ХХІ столітті - V. V. Voronov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The processes of transformation taking place in the modern world, the need to form a study the problems of the activity of economic agents (their interests, and interactions) in the plane of analysis of the transformation of material and spiritual activities reflecting its society, to identify key trends and contradictions in their development and changes in the historical socio-cultural, socio-economic dynamics. Процессы преобразований, происходящие в современном мире, формируют необходимость изучения проблем активности субъектов экономических отношений (их интересов, взаимодействия) в плоскости анализа трансформации материальной и отражающей её духовной деятельности общества, чтобы выявить основные тенденции и противоречия их развития и изменений в исторической социокультурной, социоэкономической динамике. Процеси перетворень, що відбуваються в сучасному світі, формують необхідність вивчення проблем активності суб’єктів економічних відносин у площині аналізу трансформації матеріальної духовної діяльності суспільства, щоб виявити основні тенденції і протиріччя їх розвитку і змін в історичній соціокультурній, соціоекономічній динаміці.